Modified Nutrition Risk in Critically ill is an effective nutrition risk screening tool in severely burned patients, compared with Nutrition Risk Screening 2002 - Ma, Zhenzhu; Zhang, Yin; Zhang, Qin; Wu, Beiwen (Frontiers in Nutrition, 2022)
Objective: The present study aimed to investigate prevalence of nutrition risk and evaluate the performance of NRS2002 and mNUTRIC in the prognosis of severely burned patients. Methods: The retrospective cohort study used medical data of severely burned patients admitted to the burn center of Shanghai Ruijin Hospital between January 2015 and September 2021. Demographics, clinical characteristics, laboratory nutritional indicators and NRS2002 score and mNUTRIC score were collected and analysed. Spearman correlation analysis was carried out to show the correlation between variables. The area under receiver operating characteristic (ROC) curve was used to assess the ability of NRS2002 and mNUTRIC to predict mortality and calculate optimal cutoff value. Kaplan-Meier survival curves and log-rank tests were conducted to compare the overall survival (OS). Multivariate Cox proportional hazard regression model was used to identify risk factors for 28-day mortality of severely burned patients. Results: A total of 429 adult patients with burn area larger than 30% total body surface area (TBSA) were included in this study. Incidence of nutrition risk was detected in 62.94% by NRS2002 and 52.21% by mNUTRIC. mNUTRIC was superior to NRS2002 in predicting 28-day mortality (area under ROC curve: 0.795 vs 0.726). Multivariate Cox regression analysis showed that high mNUTRIC (hazard ratio (HR) = 4.265, 95% CI = 1.469-12.380, P = 0.008) and TBSA (HR = 1.056, 95% CI = 1.033-1.079, P < 0.001) were independent predictors for 28-day mortality. After adjusting for covariates, high NRS2002 was not associated with 28-day mortality (P = 0.136). Conclusion: The present study illustrated the effectiveness of mNUTRIC as nutrition risk screening tool among severely burned patients. Early identification of nutrition risk may help to maximize benefits of nutritional therapy by providing more aggressive nutritional therapy for patients at nutrition risk.